2013
DOI: 10.1371/journal.pone.0067224
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Bifidobacterium longum subsp. infantis to Milk Oligosaccharides Increases Adhesion to Epithelial Cells and Induces a Substantial Transcriptional Response

Abstract: In this study, we tested the hypothesis that milk oligosaccharides may contribute not only to selective growth of bifidobacteria, but also to their specific adhesive ability. Human milk oligosaccharides (3′sialyllactose and 6′sialyllactose) and a commercial prebiotic (Beneo Orafti P95; oligofructose) were assayed for their ability to promote adhesion of Bifidobacterium longum subsp. infantis ATCC 15697 to HT-29 and Caco-2 human intestinal cells. Treatment with the commercial prebiotic or 3′sialyllactose did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
2
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 57 publications
8
84
2
3
Order By: Relevance
“…Chichlowski et al (27) showed that growth of B. infantis ATCC15697 on HMOs increases binding to intestinal epithelial cells in vitro, decreases release of inflammatory cytokines, and increases release of anti-inflammatory cytokines in response to an inflammatory stimulus. A similar increase in binding was determined using sialyllactose (69). These studies suggest that the specific growth phenotype of milk glycan–enriched bifidobacterial populations promotes persistence in situ and positively modulates the host epithelium.…”
Section: Establishing Structure-function Relationships Of Human Milk supporting
confidence: 67%
“…Chichlowski et al (27) showed that growth of B. infantis ATCC15697 on HMOs increases binding to intestinal epithelial cells in vitro, decreases release of inflammatory cytokines, and increases release of anti-inflammatory cytokines in response to an inflammatory stimulus. A similar increase in binding was determined using sialyllactose (69). These studies suggest that the specific growth phenotype of milk glycan–enriched bifidobacterial populations promotes persistence in situ and positively modulates the host epithelium.…”
Section: Establishing Structure-function Relationships Of Human Milk supporting
confidence: 67%
“…The species that cannot utilize HMOs have a disadvantage and do not readily colonize. However, HMOs do not only serve as substrate for bacteria but they can also enhance Bifidobacteria persistence in the gastrointestinal tract by increasing their ability to bind to epithelial cells (Chichlowski et al 2012;Kavanaugh et al 2013). In the study of Wickramasinghe and collegues (Wickramasinghe et al 2015) it was found that both strain and carbon source affect binding affinity of Bifidobacteria to epithelial cells.…”
Section: Effects Of Hmos On Microbiota Compositionmentioning
confidence: 99%
“…First, as described above, B. infantis has a competitive advantage in the presence of human milk components; therefore, increased colonization resulting in decreased diversity of the gut microbiota and fewer luminal pathogens is one likely mechanism of protection. In addition to a selective growth advantage, in vitro studies reveal that B. infantis cells grown on HMO bind to cultured intestinal cells at a higher rate suggesting that the unique ability to grow on HMOs coincides with an increased ability to bind and colonize the intestinal mucus layer (65,66). …”
Section: Mechanisms Of Observed Protective Effectsmentioning
confidence: 99%